Descriptions, notes, and a new record in Oideterus Thomson (Coleoptera, Cerambycidae, Prioninae, Anacolini) - Vlasak, Josef; Santos-Silva, Antonio (Zootaxa, 2022)
The male of Oideterus elegans (Waterhouse, 1880) is described for the first time, female chromatic variations are reported, and the species is recorded from the Ecuadorian department of Napo. Two new species are described from Ecuador: Oideterus leoninus and O. ecuadorensis. The species-group name of O. nigrum Botero, Galileo & Santos-Silva, 2019 is corrected. Identification keys to males and females of Oideterus species are provided.